Effect of MgO Contents on the Microstructure, Mechanical Properties and Corrosion Behavior of Low-Alloyed Mg-Zn-Ca Alloy - Qian Zhao; Shaoyuan Lyu; Guopeng Zhang; Minfang Chen (Metals, 2024)
The effects of different MgO contents (0.3 wt.%, 0.5 wt.%, 0.7 wt.% and 1.0 wt.%) on the microstructure and properties of Mg-1Zn-0.5Ca alloy (ZX) were systematically investigated to promote the clinical application of Mg alloys. The results showed that a MgO addition promoted the precipitates of Ca2Mg6Zn3 and Mg2Ca after hot extrusion. Meanwhile, the average grain size of the ZX alloy decreased abruptly from 17.73 μm to 5.54 μm after the addition of 0.3 wt.% MgO and then reduced slowly as further increasing the MgO contents to 1.0 wt.%. The microhardness and yield strength (YS) increased gradually from 59.43 HV and 102.0 MPa in ZX to 69.81 HV and 209.5 MPa in ZX1.0, respectively. However, the elongation to failure (EL) decreased from 26.7% in ZX to 21.2% in ZX1.0 due to the increase of volume fraction of the second phase and decrease of grain size as increasing the MgO. The corrosion result showed that ZX alloy exhibited local corrosion while ZX composites (ZX0.3, ZX0.5 and ZX0.7) displayed relatively uniform corrosion owing to the fine grain size, dispersed fine second and the protective effect of corrosion product after MgO hydrolyzation. However, excessive MgO (ZX1.0) easily caused the aggregation of itself and the precipitates and deteriorated the corrosion resistance of the material.